2016
DOI: 10.5920/bjpharm.2016.02
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sesamum gum as an excipient in matrix tablets

Abstract: In developing countries modern medicines are often beyond the affordability of the majority of the population. This is due to the reliance on expensive imported raw materials despite the abundance of natural resources which could provide an equivalent or even an improved function. The aim of this study was to investigate the potential of sesamum gum (SG) extracted from the leaves of Sesamum radiatum (readily cultivated in sub-Saharan Africa) as a matrix former. Directly compressed matrix tablets were prepared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Here, the authors focus on a polysaccharide that has been extracted and characterised in our lab (Sesamum radiatum) and reported (Nep et al, 2016a). Sesamum gum is a very abundant natural polymer extracted from the leaves of Sesamum radiatum and has been reported for having the potential for retarding drug release from matrix systems as well as having the ability to withstand hydroalcoholic media effects (Ngwuluka, Nep, Ochekpe, Odumosu, & Olorunfemi, 2014;Nep et al, 2016;2018). It has also been used to improve the dissolution behaviour of ibuprofen and as a binder (Shaboun et al, 2018;Allagh et al, 2005).…”
mentioning
confidence: 99%
“…Here, the authors focus on a polysaccharide that has been extracted and characterised in our lab (Sesamum radiatum) and reported (Nep et al, 2016a). Sesamum gum is a very abundant natural polymer extracted from the leaves of Sesamum radiatum and has been reported for having the potential for retarding drug release from matrix systems as well as having the ability to withstand hydroalcoholic media effects (Ngwuluka, Nep, Ochekpe, Odumosu, & Olorunfemi, 2014;Nep et al, 2016;2018). It has also been used to improve the dissolution behaviour of ibuprofen and as a binder (Shaboun et al, 2018;Allagh et al, 2005).…”
mentioning
confidence: 99%
“…(insert Figure 4 near here). This suggests that SGp is a highly compactible polymer as it formed the hardest compacts relative to HPMCp matrices [21,22]. In addition, there was a reduction in the porosity, and hardness of formulated compacts (SGf and HPMCf) relative to their pure polymers.…”
Section: Physical Properties Of Formulation and Formulation Blendsmentioning
confidence: 97%
“…Gum from the leaves of Sesamum indicum have been evaluated as a binder in paracetamol tablets [18] and as matrix former in tablet formulations [19]. In addition, the binding properties of gum [20] extracted from its closest specie -Sesamum radiatum and its matrices has been reported [21]. The structural properties of Sesamum radiatum gum (SG) has been elucidated and it showed that the gum from the leaves of this plant is a branched glucuronomannan [22].…”
Section: Introductionmentioning
confidence: 99%
“…Transport across this layer is by diffusion, but erosion can also occur when the polymer chains begin to untangle, as this happens the drug begins to be released [3]. The natural polymers have been used as matrices for sustained release [4][5][6][7][8][9][10][11][12] stabilizers or suspending agents in liquid dosage forms [13] and in bioadhesive drug delivery systems [14,15]. Apart from the fact that the natural materials are biocompatible, they have the additional advantages of being low cost and relatively abundant [16][17][18] compared to their synthetic counterparts.…”
Section: Introductionmentioning
confidence: 99%